2019
DOI: 10.1111/ijn.12745
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulmonary rehabilitation in elderly patients with COPD: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aim The review aimed to evaluate the effects of pulmonary rehabilitation in elderly patients with chronic obstructive pulmonary disease (COPD). Background With an increase in published reports on pulmonary rehabilitation, there is a need for a meta‐analysis to measure the effects of pulmonary rehabilitation in elderly COPD patients. Design A systematic review and meta‐analysis. Data Sources The Cochrane library (Issue 4, 2018), Web of Science (1975 to April 2018), Embase (1974 to April 2018), Pubmed (1966 to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…PR improves gait speed in many participants by increasing 6MWD. Although the duration of PR (walking as the primary exercise intervention, but also including health education, breathing training, and limb training) varied from 2 to 12 months, the mean 6MWD increased to varying degrees (62 m and 71.46 m, respectively) after completion of the program ( 54 , 55 ). This means that gait speed increased by at least 0.17 m/s, which is greater than the minimum clinical difference of 0.11 m/s in gait speed for 4MGS ( 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…PR improves gait speed in many participants by increasing 6MWD. Although the duration of PR (walking as the primary exercise intervention, but also including health education, breathing training, and limb training) varied from 2 to 12 months, the mean 6MWD increased to varying degrees (62 m and 71.46 m, respectively) after completion of the program ( 54 , 55 ). This means that gait speed increased by at least 0.17 m/s, which is greater than the minimum clinical difference of 0.11 m/s in gait speed for 4MGS ( 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation can also be addressed through the social support provided by health-care programmes such as group-based pulmonary rehabilitation. Pulmonary rehabilitation, although clinically effective, 14,15 has low uptake, 27 being offered to only 15% of patients in our linked case note review. 16 Key barriers to accessing pulmonary rehabilitation in NZ's southern region include limited geographical availability and, from a patient perspective, limited awareness of its utility and inability to travel to main centres to attend pulmonary rehabilitation classes, as reported elsewhere.…”
Section: Discussionmentioning
confidence: 85%
“…13 Pulmonary rehabilitation, usually delivered as a structured programme to a group of patients, can improve health outcomes for patients of all ages with COPD throughout the course of the disease. 14,15 This study is part of a larger research project exploring service utilisation and enablers and barriers to effective COPD care in the Southern District Health Board (DHB) region of NZ. 16,17 The study aim was to understand how patients with severe COPD experience and cope with the condition.…”
Section: Introductionmentioning
confidence: 99%
“…The complex PR has reduced the rate of dynamic hyperinflation, which is important, because dynamic hyperinflation severely limits patients' quality of life and workload respectively (33,34). The effectiveness of complex PR is supported by the highest level of evidence (35,36). Evidence-based, randomized, controlled trials have shown improved performance and quality of life in patients with COPD (12,37), regardless of the severity of their condition.…”
Section: Resultsmentioning
confidence: 99%